Overview of Typical Projects for Geological Storage of CO2 in Offshore Saline Aquifers - Lintao Li; Yuming Liu; Yanzun Li; Ziyi Wang; Kai Guo; Qianli Ma; Yingying Cui; Kaibang Liu; Cong Chen (Liquids)
With the continuous growth of global energy demand, greenhouse gas emissions are also rising, leading to serious challenges posed by climate change. Carbon Capture, Utilization, and Storage (CCUS) technology is considered one of the key pathways to mitigate climate change. Among the CCUS technologies, CO2 storage in offshore saline aquifers has gained significant attention in recent years. This paper conducts an in-depth analysis of the Sleipner and Snøhvit projects in Norway and the Tomakomai project in Japan, exploring key issues related to the application, geological characteristics, injection strategies, monitoring systems, and simulation methods of CO2 storage in offshore saline aquifers. This study finds that CO2 storage in offshore saline aquifers has high safety and storage potential but faces several challenges in practical applications, such as geological reservoir characteristics, technological innovation, operational costs, and social acceptance. Therefore, it is necessary to further strengthen technological innovation and policy support to promote the development and application of CO2 storage in offshore saline aquifers. This study provides valuable experiences and insights for similar projects worldwide, contributing to the sustainable development of CO2 storage in offshore saline aquifers and making a greater contribution to achieving global net-zero emission targets.